Domino Effects and Industrial Risks: Integrated Probabilistic Framework – Case of Tsunamis Effects - Mebarki, Ahmed; Jerez Barbosa, Sandra Rocio; Matasic, Igor; Prodhomme, Gaëtan; Reimeringer, Mathieu; Pensee, Vincent; Anh Vu, Quang; Willot, Adrien (Springer Nature, 2013)
This paper presents an integrated probabilistic framework that deals with the industrial accidents and domino effects that may occur in an industrial plant. The particular case of tsunamis is detailed in the present paper: simplified models for the inundations depths and run-ups as well as their mechanical effects on industrial tanks. The initial accident may be caused by severe service conditions in any of the tanks either under or at atmospheric pressure, or triggered by a natural hazard such as earthquake, tsunami or extreme floods for instance. This initial event generates, in general, a set of structural fragments, a fire ball, a blast wave as well as critical losses of containment (liquid and gas release and loss). The surrounding facilities may suffer serious damages and may also be a new source of accident and explosion generating afterwards a new sequence of structural fragments, fire ball, blast wave and confinement loss. The structural fragments, the blast wave form and the features of the fire ball can be described following database and feedback collected from past accidents. The surrounding tanks might be under or at atmospheric pressure, and might be buried or not, or protected by physical barriers such as walls. The vulnerability of the potential targets should therefore be investigated in order to assess the risk of propagation of the accidents since cascading sequences of accidents, explosions and fires may take place within the industrial plant, giving rise to the domino effect that threatens any industrial plant. The present research describes the risk of domino effect occurrence. The methodology is developed so that it can be operational and valid for any industrial site. It is supposed to be valid for a set of sizes, forms and kinds of tanks as well as a given geometric disposal on the industrial site. The interaction and the behavior of the targets affected or impacted by the first explosion effects should be described thanks to adequate simplified or sophisticated mechanical models: perforation and penetration of metal fragments when they impact surrounding tanks, as well as global failure such as overturning, buckling, excessive bending or shear effects, etc. The vulnerability analysis is detailed for the case of tanks under the mechanical effects generated by tsunamis.

Este documento presenta un marco probabilístico integrado que trata los accidentes industriales y los efectos dominó que pueden producirse en una planta industrial. En el presente trabajo se detalla el caso particular de los tsunamis: modelos simplificados para las profundidades de las inundaciones y los run-ups, así como sus efectos mecánicos en los tanques industriales. El accidente inicial puede ser causado por condiciones severas de servicio en cualquiera de los tanques, ya sea bajo o a presión atmosférica, o desencadenado por un peligro natural como un terremoto, un tsunami o inundaciones extremas, por ejemplo. Este evento inicial genera, en general, un conjunto de fragmentos estructurales, una bola de fuego, una onda expansiva, así como pérdidas críticas de contención (liberación y pérdida de líquidos y gases). Las instalaciones circundantes pueden sufrir graves daños y también pueden ser una nueva fuente de accidentes y explosiones generando después una nueva secuencia de fragmentos estructurales, bola de fuego, onda expansiva y pérdida de confinamiento. Los fragmentos estructurales, la forma de la onda expansiva y las características de la bola de fuego pueden describirse a partir de la base de datos y de la información recogida en accidentes anteriores. Los tanques circundantes pueden estar bajo o a presión atmosférica, y pueden estar enterrados o no, o protegidos por barreras físicas como muros. Por lo tanto, debe investigarse la vulnerabilidad de los objetivos potenciales para evaluar el riesgo de propagación de los accidentes, ya que pueden producirse secuencias en cascada de accidentes, explosiones e incendios dentro de la planta industrial, dando lugar al efecto dominó que amenaza a cualquier planta industrial. La presente investigación describe el riesgo de ocurrencia del efecto dominó. La metodología se desarrolla de forma que pueda ser operativa y válida para cualquier planta industrial. Se supone que es válida para un conjunto de tamaños, formas y tipos de depósitos, así como para una determinada disposición geométrica en el emplazamiento industrial. La interacción y el comportamiento de los objetivos afectados o impactados por los primeros efectos de la explosión deben describirse gracias a modelos mecánicos adecuados, simplificados o sofisticados: perforación y penetración de fragmentos metálicos cuando impactan en los tanques circundantes, así como fallos globales como el vuelco, el pandeo, los efectos de flexión o cizallamiento excesivos, etc. El análisis de vulnerabilidad se detalla para el caso de los tanques bajo los efectos mecánicos generados por los tsunamis. Traducción realizada con la versión gratuita del traductor www.DeepL.com/Translator
Keywords: Tsunamis; Accidentes de trabajo; Edificios industriales; Industrial buildings; Tsunamis; Industrial accidents; Explosions; Domino effect; Atmospheric tank; Tank under pressure; Risk of failure